The Investigation of Gender and Gender Roles in the Textbook Images of Pahlavi Period - Zahra Alizadeh Birjandi; Zahra Hamedi; Somayeh Poursoltani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In addition to the role of textbooks in conveying information and understanding the curriculum, they can effectively socialize and institutionalize social values. Textbooks and their illustrations have a lasting effect on learners’ attitudes and behavioral patterns by inducing content and concepts. One of the categories worth studying to understand these functions is how gender is reflected in textbook images. Therefore, in the present study, the images of elementary school books of the Pahlavi period have been examined in terms of gender and gender roles. This descriptive-analytical study aims to evaluate the role of textbook images in redefining gender roles and gender modeling of learners. The findings of this study show the effect of the presence of gender stereotypes in terms of the role and position of the two sexes in the family and the social system. The gender structure of the textbook images of the Pahlavi period indicates the limitation of the presence of women in the historical, political, scientific, and intellectual fields.